IMPACT OF SUBOXIA ON SINKING PARTICULATE ORGANIC CARBON: ENHANCED CARBON FLUX AND PREFERENTIAL DEGRADATION OF AMINO ACIDS VIA DENITRIFICATION - Van Mooy B.A.S.; Keil R.G.; Devol A.H. (My University, 2002)
Fluxes of particulate organic carbon (POC) through the oxygen deficient waters in the eastern tropical North Pacific were found to be relatively less attenuated with depth than elsewhere in the eastern North Pacific. The attenuation coefficient (b) for the flux was found to be 0.40 versus the composite value of 0.86 determined by Martin et al. (1987). To examine this further, sinking POC was collected using sediment traps and allowed to degrade in oxic and suboxic experiments. Using a kinetic model, it was found that degradation proceeded at similar rates (roughly 0.8 day-1) under oxic and suboxic conditions, but a greater fraction of bulk POC was resistant to degradation in the suboxic experiments (61% vs. 23%). Amino acids accounted for 37% of POC collected at 75m, but following degradation the value dropped to 17% and 16% in the oxic and suboxic experiments respectively. POC collected from 500m was 10% amino acids. The non-AA component of POC collected at 75m was not degraded under suboxic conditions, while under oxic conditions it was. These results suggest that microbes degrading OC under suboxic conditions via denitrification preferentially utilize nitrogen-rich amino acids. This preferential degradation of amino acids suggests that 9% more nitrogen may be lost via water column denitrification than is accounted for when a more ''Redfieldian'' stoichiometry for POC is assumed.